Pengaruh Permainan Tebak Gambar Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Di Surabaya: Pengaruh Permainan Tebak Gambar Untuk Meningkatkan Pemahaman Kosa Kata Bahasa Arab Di Surabaya - Zuhrotul Mufidah; Moch Batdrus Soleh (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
Arabic is one of the international languages ​​that is widely studied in Indonesia, especially at Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah. Arabic is considered difficult because it has a vocabulary that changes a lot in every word form. Creative educators are able to provide a pleasant classroom atmosphere. The guessing game media is one of the innovations in the learning process to create a learning atmosphere that is not boring for students. The purpose of this study was to determine the effect of using picture guessing game media in improving understanding of Arabic vocabulary in Surabaya. After giving the pre-test, it was continued to give treatment (learning) and ended by giving a post-test to determine the effect of using picture-guessing game media to improve understanding of Arabic vocabulary in Surabaya. This study uses a quantitative method with the type of experimental class research which is intended to determine whether there is a consequence of "something" imposed on the subject under study. by using the Paired Sample t-Test test data with the SPSS application. The learning process using this picture guessing game media goes through several stages, first students are given the material then asked to repeat the vocabulary, after repeating the vocabulary students are invited to play guess pictures that have previously been told how and the rules of the game. With this game students do not feel bored when the learning process takes place, without realizing it students try to remember the vocabulary that has been conveyed when guessing the picture in turn. The results of the post test scores showed an increase from the pre test results of 76%, then the data was processed using the Paired T test using SPSS, based on the results of the T test on the pre test and post test values, the T value was 24,347 while the T table value was 1,695. Based on the results of the T test, it can be concluded that the T value is greater than the T table value. So it can be stated that Hypothesis Ha is accepted and Hypothesis H0 is rejected. So the guessing game media has an effect on improving the understanding of Arabic vocabulary at Madrasah Surabaya.